The Impact of Biological Dissatisfaction of Husband and Wife on Divorce at the Religious Court of Bantaeng Regency 2021-2022 - Mahenra, Usril Asyar; Muchtar, M Ilham; Billah, Muktashim (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
This study is to determine the Impact of Biological Dissatisfaction of Married Couples on Divorce in the Bantaeng Regency Religious Court in 2021-2022, this purpose is described in sub-problems: 1. How is the picture of divorce caused by biological dissatisfaction factors of married couples that occur in the Bantaeng Regency Religious Court. 2. How the impact of biological dissatisfaction on married couples led to divorce at the Bantaeng Regency Religious Court. This research is a field research that uses a qualitative approach by conducting an interview and documentation process. The results of this study show that based on data from the Bantaeng Regency Religious Court, divorce cases in Bantaeng Regency in 2021-2022 have increased. In 2021 there were 337 divorce cases and in 2022 there were 379 divorce cases. Divorce occurs due to several factors including economic factors, family, biological dissatisfaction or other factors. 15%-25% of the total cases each year divorce due to biological dissatisfaction and partly due to other factors. And the impact of biological dissatisfaction with the couple is first, lack of respect for the partner, second, not being provided for by the husband and domestic violence.